REABILITAS PELAYANAN SURAT KETERANGAN WARIS DI KELURAHAN PARIT TOKAYA KECAMATAN PONTIANAK SELATAN - E.21108033, Hayati (FISIP Universitas Tanjungpura, 2013)
ThisÂ thesis is intended to provide an understanding of the inheritance certificate services in the Village District Ditch Tokya South Pontianak. Issues concerning the implementation of services especially regarding service certificate Certificate of Inheritance, has not been done in accordance with Law No. 25 Year 2009 on the Public Service, for services given a certificate of inheritance has not shown a series of integrated activities that are simple, transparent, smooth, precise, complete, fair and affordable like: Heritage Certificate of completion of creation sometimes beyond the time period specified, the service system is always faced with a complicated procedure, so that people find it difficult to meet the necessary requirements. The results showed that the implementation of the Inheritance Certificate services is still very far from the expected. such measures are more officers expect remuneration, if seen from the indicators used in this study. This, happens because of weak implementation of the code of ethics officers in the service, so that indicated the actions that deviate from bureaucracy as the officers who volunteered as a service bureau or brokers that lead to acts of corruption. Low awareness bureaucracy responsibility and discipline in the service process, and the persistence of discrimination that led to the service element of nepotism. In addition, less bureaucracy was able to realize the mission of the organization of the rules set out in the delivery of services to the public.Keywords:Â ReabillityÂ Services, Certificate of Waris.